A PLISSIT-BASED COMPREHENSIVE SEXUAL EDUCATION INTERVENTION ON ATTITUDES TOWARDS HIV TRANSMISSION PREVENTION IN ADOLESCENTS: A GENDER EQUALITY PERSPECTIVE - Nirwanto K. Rahim; Erwin Purwanto (PT. Jurnal Center Indonesia Publisher, 2025)
Adolescents are a vulnerable group to the risks of sexual violence and HIV transmission due to limited sexual literacy, insufficient access to accurate reproductive health information, and strong socio-cultural taboos surrounding sexuality. Comprehensive interventions are needed to equip adolescents with adequate knowledge, attitudes, and gender-sensitive decision-making skills. This study aimed to analyze the effectiveness of a PLISSIT-based Comprehensive Sexual Education intervention in improving adolescents’ attitudes toward HIV transmission prevention from a gender equality perspective. This quasi-experimental study involved 100 students selected through simple random sampling and divided into experimental and control groups. The experimental group received four PLISSIT-based educational sessions integrating gender equality principles, while the control group received conventional sexual education. Data were collected using pre- and post-test questionnaires and analyzed using the Wilcoxon signed-rank test. The results showed a substantial improvement in adolescents’ attitudes after the intervention. Prior to the intervention, only 18% of students demonstrated good attitudes toward HIV prevention, while 82% were categorized as poor. After the intervention, 90% of students in the experimental group showed good attitudes, and only 10% remained in the poor category, with a statistically significant difference (p = 0.001). These findings indicate that the PLISSIT-based comprehensive sexual education model is effective in shaping positive attitudes by providing a safe space for discussion, relevant information, and gender-responsive guidance. In conclusion, the PLISSIT-based intervention significantly enhances adolescents’ attitudes toward HIV prevention and can serve as a strategic approach in school-based reproductive health education.